Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine which point is a solution to the system of linear equations:
[tex]\[ \begin{cases} y = -x + 3 \\ 2x - y = 6 \end{cases} \][/tex]
we will substitute each point into the system of equations and see which one satisfies both equations.
Checking the point [tex]\((3, 0)\)[/tex]:
1. Substituting [tex]\((3, 0)\)[/tex] into the first equation [tex]\(y = -x + 3\)[/tex]:
[tex]\[ 0 = -3 + 3 \][/tex]
[tex]\[ 0 = 0 \quad \text{(True)} \][/tex]
2. Substituting [tex]\((3, 0)\)[/tex] into the second equation [tex]\(2x - y = 6\)[/tex]:
[tex]\[ 2(3) - 0 = 6 \][/tex]
[tex]\[ 6 = 6 \quad \text{(True)} \][/tex]
Since the point [tex]\((3, 0)\)[/tex] satisfies both equations, it is a solution to the system.
Checking the point [tex]\((3, -1)\)[/tex]:
1. Substituting [tex]\((3, -1)\)[/tex] into the first equation [tex]\(y = -x + 3\)[/tex]:
[tex]\[ -1 = -3 + 3 \][/tex]
[tex]\[ -1 = 0 \quad \text{(False)} \][/tex]
Since the point [tex]\((3, -1)\)[/tex] does not satisfy the first equation, it is not a solution.
Checking the point [tex]\((0, 3)\)[/tex]:
1. Substituting [tex]\((0, 3)\)[/tex] into the first equation [tex]\(y = -x + 3\)[/tex]:
[tex]\[ 3 = -0 + 3 \][/tex]
[tex]\[ 3 = 3 \quad \text{(True)} \][/tex]
2. Substituting [tex]\((0, 3)\)[/tex] into the second equation [tex]\(2x - y = 6\)[/tex]:
[tex]\[ 2(0) - 3 = 6 \][/tex]
[tex]\[ -3 = 6 \quad \text{(False)} \][/tex]
Since the point [tex]\((0, 3)\)[/tex] does not satisfy the second equation, it is not a solution.
Checking the point [tex]\((-1, 3)\)[/tex]:
1. Substituting [tex]\((-1, 3)\)[/tex] into the first equation [tex]\(y = -x + 3\)[/tex]:
[tex]\[ 3 = -(-1) + 3 \][/tex]
[tex]\[ 3 = 1 + 3 \][/tex]
[tex]\[ 3 = 4 \quad \text{(False)} \][/tex]
Since the point [tex]\((-1, 3)\)[/tex] does not satisfy the first equation, it is not a solution.
After checking all the points, we find that only the point [tex]\((3, 0)\)[/tex] satisfies both equations. Therefore, the point [tex]\((3, 0)\)[/tex] is the solution to the system of equations.
[tex]\[ \begin{cases} y = -x + 3 \\ 2x - y = 6 \end{cases} \][/tex]
we will substitute each point into the system of equations and see which one satisfies both equations.
Checking the point [tex]\((3, 0)\)[/tex]:
1. Substituting [tex]\((3, 0)\)[/tex] into the first equation [tex]\(y = -x + 3\)[/tex]:
[tex]\[ 0 = -3 + 3 \][/tex]
[tex]\[ 0 = 0 \quad \text{(True)} \][/tex]
2. Substituting [tex]\((3, 0)\)[/tex] into the second equation [tex]\(2x - y = 6\)[/tex]:
[tex]\[ 2(3) - 0 = 6 \][/tex]
[tex]\[ 6 = 6 \quad \text{(True)} \][/tex]
Since the point [tex]\((3, 0)\)[/tex] satisfies both equations, it is a solution to the system.
Checking the point [tex]\((3, -1)\)[/tex]:
1. Substituting [tex]\((3, -1)\)[/tex] into the first equation [tex]\(y = -x + 3\)[/tex]:
[tex]\[ -1 = -3 + 3 \][/tex]
[tex]\[ -1 = 0 \quad \text{(False)} \][/tex]
Since the point [tex]\((3, -1)\)[/tex] does not satisfy the first equation, it is not a solution.
Checking the point [tex]\((0, 3)\)[/tex]:
1. Substituting [tex]\((0, 3)\)[/tex] into the first equation [tex]\(y = -x + 3\)[/tex]:
[tex]\[ 3 = -0 + 3 \][/tex]
[tex]\[ 3 = 3 \quad \text{(True)} \][/tex]
2. Substituting [tex]\((0, 3)\)[/tex] into the second equation [tex]\(2x - y = 6\)[/tex]:
[tex]\[ 2(0) - 3 = 6 \][/tex]
[tex]\[ -3 = 6 \quad \text{(False)} \][/tex]
Since the point [tex]\((0, 3)\)[/tex] does not satisfy the second equation, it is not a solution.
Checking the point [tex]\((-1, 3)\)[/tex]:
1. Substituting [tex]\((-1, 3)\)[/tex] into the first equation [tex]\(y = -x + 3\)[/tex]:
[tex]\[ 3 = -(-1) + 3 \][/tex]
[tex]\[ 3 = 1 + 3 \][/tex]
[tex]\[ 3 = 4 \quad \text{(False)} \][/tex]
Since the point [tex]\((-1, 3)\)[/tex] does not satisfy the first equation, it is not a solution.
After checking all the points, we find that only the point [tex]\((3, 0)\)[/tex] satisfies both equations. Therefore, the point [tex]\((3, 0)\)[/tex] is the solution to the system of equations.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.